Motor and learning disabilities in school children with low academic performance - da Silva J.* (2012)
The study aimed to identify the motor and learning difficulties in students with low academic performance. Took part in the study 19 students, with 08 boys and 11 girls, mean age of 10.3 (± 1.20) years in a school, municipality of São José / SC-BR. The selection of participants occurred through the suggestion of teachers, pupils who had a history of poor academic performance during the semester. We used two scales: Movement Assessment Battery for Children and the School Performance Test. It was found that there was agreement between the results and initial indication of the teachers, as almost all pupils had learning difficulties, especially in reading and writing, as well as a representative number of students indicating they had motor difficulties. A significant number of children presented together with an indication of learning difficulties, problems with motor coordination. It is suggested to conduct research that will explore both the identification of developmental difficulties, and programs aimed at stimulating the economic well being, quality of life and health of children with learning and motor disabilities.